Teachers And Students’ Perceptions Of Technology-Based Biology Learning In Public High School 2 South Region - Rizki Nilwani, Fitri Endang Srimulat, Wita Ferwati (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The utilization of technology in learning has been an important part of the transformation of education, particularly in the subject of Biology which demands conceptual understanding and visualization of the material. The post-pandemic learning paradigm change encourages the use of digital media, Learning Management System (LMS), and various other technological applications as a means of supporting teaching-learning activities. However, the effectiveness of technology-based learning implementation is highly dependent on the perception of teachers and students as the main actors in the learning process. This study aimed to describe and analyze teachers’ and students’ perceptions towards technology-based Biology learning at Senior Secondary School 2 Southern Region. This study used a quantitative descriptive approach with a survey method. The respondents consisted of all Biology teachers and grade XI science students who were selected by total sampling for teachers and proportional random sampling for students. The research instrument was in the form of a Likert-scale questionnaire that had been validated by experts and tested for reliability